The Use of Circulating Tumor DNA to Monitor and Predict Response to Treatment in Colorectal Cancer - Reece, Mifanwy; Saluja, Hariti; Hollington, Paul; Karapetis, Christos S.; Vatandoust, Sina; Young, Graeme P.; Symonds, Erin L. (Frontiers in Genetics, 2019)
Background: Colorectal cancer is one of the most common cancers worldwide and has a high mortality rate following disease recurrence. Treatment efficacy is maximised by providing tailored cancer treatment, ideally involving surgical resection and personalised neoadjuvant and adjuvant therapies, including chemotherapy, radiotherapy and increasingly, targeted therapy. Early detection of recurrence or disease progression results in more treatable disease and is essential to improving survival outcomes. Recent advances in the understanding of tumour genetics have resulted in the discovery of circulating tumour DNA (ctDNA). A growing body of evidence supports the use of these sensitive biomarkers in detecting residual disease and diagnosing recurrence as well as enabling targeted and tumour-specific adjuvant therapies. Methods: A literature search in Pubmed was performed to identify all original articles preceding April 2019 that utilise ctDNA for the purpose of monitoring response to colorectal cancer treatment. Results: 92 clinical studies were included. These studies demonstrate that ctDNA is a reliable measure of tumour burden. Studies show the utility of ctDNA in assessing the adequacy of surgical tumour clearance and changes in ctDNA levels reflect response to systemic treatments. ctDNA can be used in the selection of targeted treatments. The reappearance or increase in ctDNA, as well as the emergence of new mutations, correlates with disease recurrence, progression and resistance to therapy, with ctDNA measurement allowing more sensitive monitoring than currently used clinical tools. Conclusions: ctDNA shows enormous promise as a sensitive biomarker for monitoring response to many treatment modalities and for targeting therapy. Thus, it is emerging as a new way for guiding treatment decisions – initiating, altering and ceasing treatments, or prompting investigation into the potential for residual disease. However, many potentially useful ctDNA markers are available and more work is needed to determine which are best suited for specific purposes and for improving specific outcomes.